Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

NO LINKS!!!
4. Given a term in the sequence and the common difference (d), write the equation of the sequence in the form t(n) = mn + b. Part 1

a. t(34)= 249, difference = 8

b. t(36)= 276, difference = 7

c. t(40) = -1191, difference= -30

d. t(12)= 28.6, difference= 1.8


Sagot :

Answer:

  a) t(n) = 8n -23

  b) t(n) = 7n +24

  c) t(n) = -30n +9

  d) t(n) = 1.8n +7

Step-by-step explanation:

The general equation for the n-th term of an arithmetic sequence is ...

  an = a1 +d(n -1)

Expanding this, we find ....

  an = a1 +d·n -d = d·n +(a1 -d)

Comparing that to the form ...

  an = m·n +b

we see that ...

  m = d

  b = (a1 -d)

If you're given a term other than a1, say ak, then you have ...

  ak = d·k +(a1 -d)

  (a1 -d) = ak -d·k

For a given term and common difference, we can write the desired equation as ...

  t(n) = d·n +(ak -d·k) . . . . . . given t(k) = ak and d

__

Once again, it is convenient to use a spreadsheet to do the calculations for a number of different instances of this problem.

a) t(n) = 8n -23

b) t(n) = 7n +24

c) t(n) = -30n +9

d) t(n) = 1.8n +7

View image sqdancefan